Characterization of Metglas/poly(vinylidene fluoride)/Metglas magnetoelectric laminates for AC/DC magnetic sensor applications. (15th February 2016) - Reis, S.; Silva, M.P.; Castro, N.; Correia, V.; Martins, P.; Lasheras, A.; Gutierrez, J.; Barandiarán, J.M.; Rocha, J.G.; Lanceros-Mendez, S.
Abstract: Polymer-based magnetoelectric materials show increasing interest for a large number of applications and, in particular, for the development of magnetic sensors. Nevertheless, relevant parameters such as sensitivity, accuracy, linearity, hysteresis and resolution have been vaguely or never discussed. This work reports on those parameters on a Metglas/poly(vinylidene fluoride)/Metglas magnetoelectric laminate. The sensitivity and resolution determined for the DC (30 mV·Oe − 1 and 8 μOe) and AC magnetic field sensor (992 mV·Oe − 1 and 0.3 μOe) are favorably comparable with the most sensitive polymer-based ME sensors. Further, the correlation coefficient, linearity and accuracy values are 0.995, 95.9% and 99.4% for the DC magnetic field sensor and 0.9998, 99.4% and 99.2% for the AC magnetic field sensor. Therefore, the magnetoelectric materials reported in the present study can be used for innovative AC/DC magnetic field sensors. Graphical abstract: Highlights: A Metglas/Poly(vinylidene fluoride)/Metglas laminate based magnetoelectric sensor is proposed. Sensitivity and resolution values were 30 mV.Oe − 1 and 8 μOe (DC sensor); and 992 mV.Oe − 1 and 0.3 μOe (AC sensor). r 2 coefficient, linearity and accuracy values were 0.995, 95.9% and 99.4% (DC sensor); and 0.9998, 99.4% and 99.2% (AC sensor). Sensor feature values are positively comparable with the best reported certifying its applicability as disruptive sensors.